The Top 100 High-Impact Papers in Colombian Psychology: a bibliometric study from wos and scopus - Cudina, Jean Nikola; Ossa, Julio César (Informação & Sociedade, 2016)
The goal of this research is to identify the top high-impact papers in Colombian psychology and to analyze their characteristic in order to supply information about the development of the discipline in the last decades. The research was performed with the analysis of the academic production in Colombian psychology found in the journals specialized in the discipline. The impact of the Colombian academic production is determined from the results given by the data bases WoS and Scopus. There is a low consumption index from the academic community of psychologists in Colombia. The impact of the academic production in Colombian psychology is the result of a network made up of national researchers with the international academic community located in USA and Europe. 82% of these publications are done in international journals and 77% of these are in English. The Colombian psychology fields generating the highest impact in academic productions are: Neuropsychology (34%), Clinical (25%), Social (30%), Education (3%) Experimental (2%) Organizational (3%) and Cognitive (3%). The network created between the national academic community and the Latin American is very incipient. This illustrates weaknesses which require strengthening from institutional structures and the improvement of the quality of the fundamental Colombian psychology journals in order for the discipline to move forward in our country. The development of the academic production in Colombia is very recent and it finds itself in the consolidation stage. A more substantial networking infrastructure is required by the academic community in our country to achieve a far-reaching academic production with a high impact.